2019
DOI: 10.1021/jacs.9b12186
|View full text |Cite
|
Sign up to set email alerts
|

Oriented Internal Electrostatic Fields Cooperatively Promote Ground- and Excited-State Reactivity: A Case Study in Photochemical CO2 Capture

Abstract: Oriented electrostatic fields can exert catalytic effects upon both the kinetics and thermodynamics of chemical reactions; however, the vast majority of studies thus far have focused upon ground state chemistry and rarely consider any more than a single class of reaction. In the present study, we first use density functional theory (DFT) calculations to clarify the mechanism of CO2 storage via photochemical carboxylation of o-alkylphenyl ketones, originally proposed by Murakami et al. (J. Am. Chem. Soc. 2015, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
72
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 36 publications
2
72
0
Order By: Relevance
“…This work has included (i) the use of bulk, homogeneous electric fields, 6–8 (ii) the study of anion effects on reaction selectivity, 9 (iii) the study of electrostatic stabilization of in situ -generated radical species, 10–14 and (iv) in-depth computational studies on reaction barrier (de)stabilization of organic molecules bearing charged functional groups. 15–20 Limited examples are known of transition metal complexes that use oriented internal electrostatic fields to tune the properties of the system. The Tolman group reported cupric hydroxide compounds bound by NNN pincer-type bis(carboxamide)pyridine ligands, wherein charged residues were incorporated at the para positions of the carboxamide aryl rings.…”
Section: Introductionmentioning
confidence: 99%
“…This work has included (i) the use of bulk, homogeneous electric fields, 6–8 (ii) the study of anion effects on reaction selectivity, 9 (iii) the study of electrostatic stabilization of in situ -generated radical species, 10–14 and (iv) in-depth computational studies on reaction barrier (de)stabilization of organic molecules bearing charged functional groups. 15–20 Limited examples are known of transition metal complexes that use oriented internal electrostatic fields to tune the properties of the system. The Tolman group reported cupric hydroxide compounds bound by NNN pincer-type bis(carboxamide)pyridine ligands, wherein charged residues were incorporated at the para positions of the carboxamide aryl rings.…”
Section: Introductionmentioning
confidence: 99%
“…12 While these experiments are difficult to scale for chemical synthesis, we have shown that the electric fields from remote charged functional groups, embedded on the substrate or a catalyst, can be used to catalyse chemical reactions and alter their outcome. [13][14][15][16][17][18][19][20][21][22][23][24][25] The charged group can be a Lewis acid, or an acid or base, whose charge and hence electric field, can be altered with pH. While again much of the work to date has been computational, experiments have validated these predictions in a growing number of systems.…”
Section: Introductionmentioning
confidence: 99%
“…Or indeed, solvents could be pre-ordered in other ways such as using microfluidics. 24 The structures are rendered using CYLview program. 52 In this work, we use both Drude oscillator based polarizable classical molecular dynamic (MD) simulations and multiscale quantum chemical calculations to determine if an ordered solvent environment is enough to catalyse a chemical reaction in the absence of an applied electric field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Predicting the impact of chemical modification, or application of OEFs, on photoactivity is not straightforward as different excited states have different polarities and polarizabilities and thus respond differently. 9,10,15 This in turn has complex follow-on effects on intersystem crossing rates, triplet lifetimes and other factors affecting photodissociation.…”
mentioning
confidence: 99%